2016
DOI: 10.1111/vsu.12528
|View full text |Cite|
|
Sign up to set email alerts
|

High‐Definition Video Telescope‐Assisted Ventral Slot Decompression Surgery for Cervical Intervertebral Disc Herniation in 30 Dogs

Abstract: The VITOM™ ventral slot decompression technique was fast and easy to perform. It allowed a minimally invasive approach with a small ventral slot while improving spinal cord visualization. The results of this study support the use of the VITOM™ technique in spinal veterinary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…Numerous surgical techniques have been described to treat cervical IVDH, including ventral fenestration, hemilaminectomy, dorsal laminectomy, ventral slot decompression (VSD) and modified slanted slot . Standard VSD is considered an effective and relatively safe procedure, because it provides access to the floor of the vertebral canal, enabling the removal of the ventrally located extruded nucleus pulposus and/or the protruded annulus fibrosus .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous surgical techniques have been described to treat cervical IVDH, including ventral fenestration, hemilaminectomy, dorsal laminectomy, ventral slot decompression (VSD) and modified slanted slot . Standard VSD is considered an effective and relatively safe procedure, because it provides access to the floor of the vertebral canal, enabling the removal of the ventrally located extruded nucleus pulposus and/or the protruded annulus fibrosus .…”
mentioning
confidence: 99%
“…Numerous surgical techniques have been described to treat cervical IVDH, including ventral fenestration, hemilaminectomy, dorsal laminectomy, ventral slot decompression (VSD) and modified slanted slot . Standard VSD is considered an effective and relatively safe procedure, because it provides access to the floor of the vertebral canal, enabling the removal of the ventrally located extruded nucleus pulposus and/or the protruded annulus fibrosus . Reported complications associated with the VSD procedure include incomplete decompression, severe haemorrhage and damage to vital structures—such as the trachea, oesophagus, recurrent laryngeal nerve and carotid sheath—in addition to vertebral instability and cardiopulmonary arrest …”
mentioning
confidence: 99%
“…Of the French bulldogs presented with cervical hyperaesthesia, 84 per cent were diagnosed with IVDE, which is consistent with results of a previous studies. 46 CSM, IVDP and SM all presented with a chronic onset of clinical signs. Unsurprisingly, dogs presenting with CSM typically weighed >40 kg, while SM patients were typically <10 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical loupes are popular among neurosurgeons but offer only limited magnification. The use of exoscopes and endoscopes has been reported in a few veterinary reports . Video‐assisted ventral slots have been used in cadavers and in clinically affected dogs, whereas mostly cadaveric studies have been reported for the thoracolumbar and lumbosacral region, with only one report of using an endoscope in a study in live dogs .…”
Section: Discussionmentioning
confidence: 99%